THE PLACE OF MUSIC EDUCATION IN PRESCHOOL EDUCATIONAL ORGANIZATIONS - Ravendr Kumar (International Journal of Literature and Language Studies, 2022)
This article describes the role of music education in the education of preschool children, the impact of musical activity during lessons on the child's mind, intellectual and emotional development, as well as the effective organization of music classes in preschool educational organizations and its methodological foundations.